Exploring the Anti-Obesity Effects of Prebiotics and Probiotics in Rats; An Experimental Study - Ajet Kumar; Syed Mahboob Alam; Syeda Zain; Saeeda Naseer Mengal; Rozina Fazal; Abdul Waheed Solangi (ziauddin University, 2024)
Background: Excessive body fat, or obesity, poses a significant global health concern. Research has highlighted the connection between gut microbiota and obesity. This study aimed to investigate whether the administration of prebiotics and probiotics significantly contributes to controlling obesity in a rat model with induced obesity through a high-fat diet (HFD). Methods: This experimental study involved 50 healthy male Albino Wistar Rats, aged between 10-14 weeks and weighing between 140-180 grams, whereas female rats and rats with any disease were excluded. They were divided into five groups: control (G-I), HFD alone (G-II), Prebiotic + HFD (G-III), Probiotics + HFD (G-IV), and Prebiotic + Probiotics + HFD (G-V). Data were analyzed using SPSS version 22, calculating Mean±S.D. ANOVA and post-hoc tests assessed weight changes between groups, with p-values ≤0.05 considered statistically significant. Results: Weight changes were observed across all groups on days 0, 35, and 98. The percentages of mean weight change from day 0 to 98 were as follows: G-I, 11.08%; G-II, 47.98%; G-III, 29.88%; G-IV, 29.58%; and G-V, 20.54%. Significant differences (p<0.001) were noted among the groups. Conclusion: Results in our study indicated that the inclusion of prebiotics and probiotics in the diet of rats following an HFD yields a beneficial outcome in terms of reduction of body weight. This positive effect is attributed to the stimulation and enhancement of the activity of beneficial gut bacteria. The synergistic interaction between prebiotics, probiotics, and the gut microbiota shows promise in mitigating obesity through targeted dietary interventions.